DIVERSITY OF REEF FISH FUNGSIONAL GROUPS IN TERMS OF CORAL REEF RESILIENCES - Isa Nagib edrus; Muhammad Abrar Abrar (Research Center for Fisheries, 2016)
Infrastructure development in the particular sites of Seribu Islands as well as those in main land of Jakarta City increased with coastal population this phenomenon is likely to increase the effects to the adjacent coral waters of Seribu Islands. Chemical pollutants, sedimentation, and domestic wastes are the common impact and threatening, the survival of coral reef ecosystem. Coral reef resiliences naturaly remained on their processes under many influences of supporting factors. One of the major factor is the role of reef fish functional groups on controling algae growth to recolonize coral juveniles. The aim of this study to obtain data of a herbivory and other fish functional groups of reef fishes in the Pari Islands that are resilience indicators, or that may indicate the effectiveness of management actions. A conventional scientific approach on fish diversity and abundance data gathering was conducted by the underwater visual cencus. Diversity values of the reef fish functional groups, such as the abundance of individual fish including species, were collected and tabulated by classes and weighted as a baseline to understand the resilience of coral reed based on Obura and Grimsditch (2009) techniques. The results succesfully identified several fish functional groups such as harbivores (21 species), carnivores (13 species) and fish indicator (5 species) occurred in the area. Regarding the aspects of fish density and its diversity, especially herbivorous fish functional group, were presumably in the state of rarely available to support the coral reef resiliences. Resilience indices ranged from 1 (low level) to 3 (moderate level) and averages of the quality levels ranged from 227 to 674. These levels were inadequate to support coral reef recolonization.